Monumen Jenderal Sudirman: Peranannya bagi Masyarakat Pacitan dalam Perspektif Sosial, Ekonomi, dan Pendidikan - sri dwi ratnasari (LPPM Press, 2016)
For past years, many tended to avoid the historic discussion on behalf of the futuristicplan. This research came to prove how important the history was. This research aimedat revealing (1) the historical review of Monument Jenderal Sudirman establishment inPacitan, (2) the management of Monument Jenderal Sudirman in Pacitan, and (3) therole of Monument Jenderal Sudirman towards society Pacitan in a social perspective,economic, and education. The research was carried out in the area of Monument JenderalSudirman, Pakis Baru village, Sub-district Nawangan Pacitan. Meanwhile, the descriptivequalitative research methods were employed to uncover such issues. Furthermore,the data were collected through literature, archival study, interview and observation.The dependability of the data was fulfilled by means of triangulation. The data wereprocessed through an interactive model, ie the interaction between the three componentsof the analysis (data reduction, data presentation and verification) interacted with datacollection to obtain the credible facts. The monument of general Sudirman was locatedin Nawangan history (the tourist area), there was a gate area of the monument, relief,statue of general Sudirman and the headquarters of the guerrilla. The monument wascontinuously developed to be a tourist area history. The role of the historical monumentsas tourist area can be viewed from the people perspective who see the existence of themonument as a place for recreation, earning a jobs, and conducting a research.